Cardiac Fibroblast p38 MAPK: A Critical Regulator of Myocardial Remodeling - Turner, Neil A.; Blythe, Nicola M. (Journal of cardiovascular development and disease, 2019)
The cardiac fibroblast is a remarkably versatile cell type that coordinates inflammatory, fibrotic and hypertrophic responses in the heart through a complex array of intracellular and intercellular signaling mechanisms. One important signaling node that has been identified involves p38 MAPK; a family of kinases activated in response to stress and inflammatory stimuli that modulates multiple aspects of cardiac fibroblast function, including inflammatory responses, myofibroblast differentiation, extracellular matrix turnover and the paracrine induction of cardiomyocyte hypertrophy. This review explores the emerging importance of the p38 MAPK pathway in cardiac fibroblasts, describes the molecular mechanisms by which it regulates the expression of key genes, and highlights its potential as a therapeutic target for reducing adverse myocardial remodeling.